Eksperimen Konsumsi Beberapa Jenis Bahan Bakar Pada Mesin Diesel 7 HP Silinder Tunggal - Barokah Barokah; Muhammad Bintang Fikri; Ahmad Tubagus Tsani Risqi Aji; Marinus Tappy; Wiratno Wiratno; Putu Deny Darmawan (Departemen Teknik Kelautan Universitas Hasanuddin, 2023)
The use of fuel oil to generate heat or power in the industrial world is still a major concern for researchers. Fuel quality, performance, emissions, and economic factors are some of the parameters that need to be considered for various types of fuel. In Indonesia, there are several types of diesel fuel including Pertamina Dex, Dexlite and Biosolar (B30). Of course, these fuels have different characteristics. To be able to know the character of the fuel, it is necessary to test the fuel on a diesel engine. In this study, an experiment was carried out using this fuel in a Jianfa brand diesel engine with a power of 7 HP type R175A without load with various variations of rpm, namely 1000, 1200, 1400, 1600, 1800, 2000, 2200. The experiment applies to three types of fuel, namely Biosolar (B30), Pertamina Dex, and Dexlite. Consumption is measured in units of time (seconds) per 50 milliliters. From the experiments it was found that Biosolar (B30) occupies the lowest position as evidenced by the duration of time to spend 50 milliliter at 2000 rpm only takes 49 seconds, Dexlite 63 seconds while Pertamina Dex 70 seconds. So it can be concluded that Pertamina Dex is the most economical compared to Dexlite and Biosolar (B30).